Constituency candidates in comparative perspective – How personalized are constituency campaigns, why, and does it matter?. (September 2015) - Zittel, Thomas
Abstract: The personalization of politics is a widely debated phenomenon in the electoral studies literature. However, most of the available research focuses on the national level and thus on party leaders and main party candidates. This article emphasizes the use of extending this debate to the constituency level and to constituency candidates. It furthermore sketches a framework for related research and introduces a new set of data collected in the context of the Comparative Candidate Studies Network (CCS). Highlights: Article focuses on the quantity and quality of personalization at the constituency level. Proposes a comparative framework for researching grassroots personalization. Emphasizes that different candidate centered electoral systems differ in their effects on campaign behavior. Highlights party organizational contexts as a main alternative factor interacting with electoral contexts.